A Retrospective Case Series of Concomitant Carbapenem and Valproic Acid Use: Are Best Practice Advisories Working?. (June 2023) - Fratoni, Andrew J.; Colmerauer, Jessica L.; Linder, Kristin E.; Nicolau, David P.; Kuti, Joseph L.
Background: A Best Practice Advisory (BPA) warns clinicians of an interaction between carbapenems and valproic acid (VPA) that can cause significant declines in VPA levels leading to serious consequences for patients treated for seizure disorder and unknown implications for alternative indications.Objective: The goal of this study was to assess BPA efficacy in avoiding concomitant VPA/carbapenems, and to characterize use of these agents, clinical implications, and potential alternative therapeutic options.Methods: Retrospective chart review was performed on all patients over the course of 1 year who were concomitantly prescribed a carbapenem and VPA at Hartford Hospital, Hartford, CT. Data collected included: level of care, duration of concomitant therapy, indications, VPA levels during or surrounding overlap, documentation of the interaction, and therapeutic implications.Results: Carbapenems and VPA were administered to 591 and 625 patients, respectively; the BPA fired 126 times in 24 patients, and 15 patients were initiated on these agents concomitantly. Eight (53%) patients received VPA for seizures. The remaining seven (47%) received VPA for alternative indications. Eight of nine VPA levels were sub-therapeutic during carbapenem therapy and polypharmacy was administered in all patients receiving VPA for non-convulsive indications.Conclusion: Co-prescribing of these drugs was rare; however, the BPA was ineffective in 63% of instances. Reductions in VPA efficacy for any indication should be expected with concomitant carbapenem administration. Antibiotics other than carbapenems should be considered when coverage of multidrug resistant Gram-negative pathogens is required in patients whose VPA treatment cannot be interrupted or switched to a therapeutic alternative.